Biomechanical factors behind toe clearance during the swing phase in hemiparetic patients*. Issue 3 (3rd April 2017) - Matsuda, Fumihiro; Mukaino, Masahiko; Ohtsuka, Kei; Tanikawa, Hiroki; Tsuchiyama, Kazuhiro; Teranishi, Toshio; Kanada, Yoshikiyo; Kagaya, Hitoshi; Saitoh, Eiichi
Abstract : Background: The toe clearance of a paretic limb in the swing phase of gait is related to tripping, which is considered a major cause of falls. The biomechanical factors for obtaining toe clearance are more complicated in hemiparetic gait than that in normal gait because of the compensatory movements during swing phase. Understanding the biomechanical factors should help in targeting the point for rehabilitative interventions. Objective: To clarify the biomechanical factors behind toe clearance during swing phase in hemiparetic gait. Methods: Fifty patients with hemiparesis after a stroke participated in this study. Three-dimensional motion analysis was used for the kinematic analysis of the hemiparetic gait. The correlation coefficients between limb shortening and angle changes and between limb shortening and hip elevation and foot lateral shift were calculated. Limb shortening was defined as the shortening of the hip–toe distance. The significant factors that determine toe clearance were examined by multiple regression analysis. Independent variables were limb shortening, hip elevation, and foot lateral shift. Results: Limb shortening was negatively correlated with hip elevation ( r = −0.75) and foot lateral shift ( r = −0.41). Multiple regression analysis showed a significant contribution of limb shortening and hip elevation to toe clearance. The coefficient of determination was 0.95. Conclusions: Toe clearance was mainly determined by limb shortening and hip elevation, which were found to be in a trade-off relationship. These results warrant further investigation into the use of three-dimensional motion analysis in the rehabilitation clinic to facilitate targeted rehabilitative training to restore gait ability.